PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA MODEL INKUIRI TERBIMBING UNTUK MELATIHKAN KINERJA ILMIAH SISWA - Pradianti, Dian; Wasis, Wasis; Agustini, Rudiana (JPPS (Jurnal Penelitian Pendidikan Sains), 2015)
This research aims to produce physics teaching material through guided inquiry model which is valid, practical, and effective to facilitate the students? scientific skill  in senior high school. The development of teaching material used the Kemp model and was tested in class X MIA of SMAN 1 Pasir Belengkong first semester in academic year 2014/2015 by using the one-group pretest-posttest design. The data collection used Validation, observation, tets, and questionnaire student responses. The data analysis techniques used quantitativ and qualitativ descriptive analysis. The results of this research are:1) Teaching material developed has a valid category; 2) The practicality of teaching material in terms of a good category in feasibility of lesson plans and the students? activities in accordance with steps of guided inquiry model; and 3) The teaching material effectiveness in terms of: (a) Improving students? learning achievement seen with high gain scores; (b)  Percentage of scientific skill of students indicated by the increased of each meeting; and (c) The students?responds toward material and implementation of learning are positive. Based on the result of the above  It?s conclusion that the teaching material through guided inquiry model are valid, practical, and effective  so that used to facilitate the students scientific skill in senior high school. Penelitian ini bertujuan untuk menghasilkan perangkat pembelajaran fisika model inkuiri terbimbing yang valid, praktis, dan efektif untuk melatihkan kinerja ilmiah siswa SMA. Pengembangan perangkat pembelajaran menggunakan model Kemp dan diujicobakan di kelas X MIA SMAN 1 Pasir Belenkong semester genap tahun ajaran 2014/2015 dengan one-group pretest-posttest design. Pengumpulan data menggunakan metode validasi, observasi, tes, dan angket respon siswa. Teknik analisis data menggunakan analisis kuantitatif dan deskriptip kualitatif. Temuan hasil penelitian, yaitu: 1) Perangkat pembelajaran yang dikembangkan berkategori valid; 2) Kepraktisan perangkat pembelajaran ditinjau dari keterlaksanaan RPP berkategori baik dan aktivitas siswa sesuai dengan tahap-tahap pada model inkuiri terbimbing; dan 3) Keefektifan perangkat pembelajaran ditinjau dari: (a) Peningkatan hasil belajar siswa rata-rata tinggi; (b) Persentase kinerja ilmiah siswa ditunjukkan dengan meningkatnya setiap pertemuannya; dan (c) Respon siswa terhadap perangkat dan pelaksanaan pembelajaran positif. Berdasarkan hasil-hasil di atas disimpulkan bahwa perangkat pembelajaran model inkuiri terbimbing yang dikembangkan valid, praktis, dan efektif  sehingga layak digunakan untuk melatihkan kinerja ilmiah siswa SMA.